2003
DOI: 10.1016/s1525-0016(02)00047-3
|View full text |Cite
|
Sign up to set email alerts
|

Stable genetic modification of human embryonic stem cells by lentiviral vectors

Abstract: Human embryonic stem (hES) cells are pluripotent cells derived from the inner cell mass of the early preimplantation embryo. An efficient strategy for stable genetic modification of hES cells may be highly valuable for manipulating the cells in vitro and may promote the study of hES cell biology, human embryogenesis, and the development of cell-based therapies. Here, we demonstrate that vectors derived from self-inactivating (SIN) human immunodeficiency virus type 1 (HIV-1) are efficient tools for stable genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(163 citation statements)
references
References 22 publications
5
154
0
4
Order By: Relevance
“…This is in agreement with a previous study that showed no defects in hESC differentiation in vitro (EB formation) or in vivo (teratoma formation). 8 However, at higher viral loads, we observed aberrant cell function in MSCs and hESCs. We presume that these effects are due to genomic damage as a result of multiple viral insertions, highlighting the need for further studies to assess the effect of viral copy number on stem cell function.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This is in agreement with a previous study that showed no defects in hESC differentiation in vitro (EB formation) or in vivo (teratoma formation). 8 However, at higher viral loads, we observed aberrant cell function in MSCs and hESCs. We presume that these effects are due to genomic damage as a result of multiple viral insertions, highlighting the need for further studies to assess the effect of viral copy number on stem cell function.…”
Section: Discussionmentioning
confidence: 74%
“…Given the recent use of viral vectors for ex vivo manipulation of stem cells in clinical trials, 26 we therefore investigated whether a series of lentiviral vectors could be used to manipulate gene expression in pluripotent hESCs that have the potential to differentiate into all cell types and in adult MSCs that are lineage restricted to mesoderm fates. Although it has been previously reported that lentiviral vectors can transduce both cell types, 7,8,13 we wanted to expand these studies further by demonstrating that modified lentiviral vectors can be used for complex manipulation of stem cell gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although efficient and stable gene transfer into primate ES cells would be useful for such purposes, it has been difficult and only lentiviral vectors have been successful in achieving it. [3][4][5] We have previously developed Sendai virus (SeV) vectors that replicate in the form of negative-sense single-stranded RNA in the cytoplasm of infected cells and do not go through a DNA phase. 6 SeV vectors can efficiently introduce foreign genes without toxicity into airway epithelial cells, 7 vascular tissue, 8 skeletal muscle, 9 synovial cells, 10 retinal tissue, 11 and hematopoietic progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Os retrovírus são considerados veículos naturais de transferência de material genético ao genoma de células de mamíferos (LINNEY et al, 1999;HOUDEBINE 2002). Por meio de uma inserção aleatória da construção de interesse no genoma hospedeiro, os retrovirus possuem o potencial de promover uma transdução eficiente, estável e duradoura em uma grande variedade de tipos celulares in vitro e in vivo (GROPP et al, 2003;HOFFMAN et al, 2003). Além disso, em relação aos outros vírus componentes da família dos retrovírus, os lentivírus apresentam vantagens.…”
Section: Transferência Nuclearunclassified